let A and B be bounded nonempty subset of R, and let A+B:={a+b:a element A,b element B}.
prove that the Sup(A+B)=Sup A + Sup B and inf (A+B)= inf A + inf B.
1
Expert's answer
2011-08-18T05:39:36-0400
Let us show that Sup(A+B)=Sup A + Sup B By definition x=Sup A if x>=a for any a from A, and for any t>0 there exists b from A such that b > x-t First we show that (*) Sup(A+B) <= Sup A + Sup B Let x=Sup A, y=Sup B, z=Sup(A+B)
Then x>=a for any a from A, and y>=b for any b from A, hence x+y >= a+b for any a from A and any b from B, in other words, x+y >= c for any c from A+B.
This implies (*).
To prove the inverse inequality (**) Sup(A+B) >= Sup A + Sup B that is z >= x+y suppose that z<x+y. Then there exists t>0 such that z+ 2t < x+y. In other words, z < (x-t) + (y-t).
But then there exist a from A and b from B such that x-t < a and y-t < b. On the other hand a+b <= z.
Thus we obtain that a+b <= z < x-t + y-t < a+b, which is impossible. This proves (**), and all the identity Sup(A+B)=Sup A + Sup B ======================================== The proof of inf (A+B)= inf A + inf B is analogous.
Moreover, if we denote by -A the folowing set -A = { -a | a from A } consisting of numbers opposite to numbers from A, then inf A = -sup(-A).
Hence inf (A+B)= - sup (-A-B) = - sup (-A) -sup(-B) = inf A + inf B.
Comments
Leave a comment